STRATEGI PENGEMBANGAN BENIH PADI BERSERTIFIKAT DI DESA WEIHURA KECAMATAN WANOKAKA KABUPATEN SUMBA BARAT - Didu, Yohanis Jeiwu; Wadu, Junaedin (Agros Journal of Agriculture Science, 2024)
This research aims to analyze internal and external factors that are strengths, weaknesses, opportunities and threats and determine strategies for developing certified rice seeds in Weihura Village, Wanukaka District. This type of research is quantitative descriptive research using survey methods. The source of informants in this research was 21 people. The sampling method is the accidential sampling method. The data analysis method in this research uses SWOT analysis with stages, namely determining the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE) Internal External (IE) Matrix, Strengths, Weaknesses, Opportunities, Threats (SWOT) Matrix, Quantitative Strategic Planning Matrix (QSPM). The research results show that the internal factor which is the main strength is already using a cleaning machine, the main weakness is the excessive use of pesticides. Meanwhile, the external factor that is the main opportunity is that the government continues to encourage farmers to use certified seeds, and the main threat is pest and disease attacks. The main strategy in developing certified rice seeds is to utilize the role of good farmer institutions in the process to strengthen the position of developing certified rice seeds. Keywords: SWOT; development strategy; certified rice seeds INTISARIPenelitian ini bertujuan untuk menganalisis faktor internal dan eksternal yang menjadi kekuatan, kelemahan, peluang dan ancaman serta menetapkan strategi dalam pengembangan benih padi bersertifikat di Desa Weihura Kecamatan Wanukaka. Jenis penelitian ini adalah penelitian deskriptif kuantitatif dengan menggunakan metode survei. Sumber informan dalam penelitian ini berjumlah 21 orang. Metode penentuan sampel adalah metode accidential sampling. Metode analisis data dalam penelitian ini menggunakan anaisis SWOT dengan tahapan yaitu menentukan matriks Internal Factor Evaluation (IFE), Eksternal Factor Evaluation (EFE) Internal Eksternal (IE), Matriks Strengh, Weakneses, Opportunities, Threats (SWOT), Matriks Quantitative Strategic Planning Matrix (QSPM). Hasil penelitian menunjukan bahwa faktor internal yang menjadi kekuatan utama adalah sudah menggunakan alat mesin pembersih, kelemahan utama penggunaan pestisida yang berlebihan. Sedangkan, faktor eksternal yang menjadi peluang utama adalah pemerintah terus menganjur petani menggunakan benih bersertifikat, serta ancaman utama yaitu serangan hama dan penyakit. Strategi utama dalam pengembangan benih padi bersertifikat  adalah memanfaatkan peran kelembagaan petani yang baik dalam proses untuk memperkuat posisi pengembangan benih padi bersertifikat. Kata kunci: SWOT, strategi pengembangan, benih padi bersertifikat